2020
DOI: 10.1021/acs.jmedchem.0c00413
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Dengue and West Nile Virus Protease Inhibitors with Submicromolar Activity in Reporter Gene DENV-2 Protease and Viral Replication Assays

Abstract: Dengue and West Nile virus are rapidly spreading global pathogens for which no specific therapeutic treatments are available. One of the promising targets for drug discovery against dengue and other flaviviruses is the viral serine protease NS2B-NS3. We present the design, synthesis, and in vitro and cellular characterization of a novel chemotype of potent small-molecule non-peptidic dengue protease inhibitors derived from 4-benzyloxyphenylglycine. A newly developed luciferase-based DENV-2 protease reporter sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…Substrates 7 and 8 are substrates developed and routinely used in our group for the dengue virus and West Nile virus NS2B/NS3 protease assays, and they were used here as negative controls. 39 , 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrates 7 and 8 are substrates developed and routinely used in our group for the dengue virus and West Nile virus NS2B/NS3 protease assays, and they were used here as negative controls. 39 , 40 …”
Section: Resultsmentioning
confidence: 99%
“…Substrates 7 and 8 are substrates developed and routinely used in our group for the dengue virus and West Nile virus NS2B/NS3 protease assays, and they were used here as negative controls. 39,40 We first screened the activity of the protease at a substrate concentration of 50 µM. The highest cleavage was observed for substrates 3 and 4 (Fig.…”
Section: Substrate Characterizationmentioning
confidence: 99%
“…Substrates 7 and 8 are substrates developed and routinely used in our group for the dengue and West Nile vims NS2B/NS3 protease assays, and were used here as negative controls. 36–37…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are decarboxylated peptides containing a C-terminal 4-guanidinobenzylamino group which is responsible for interacting with S1 pocket of the protease. The most potent inhibitor obtained in these studies (5) showed a EC 50 value of 0.5 mM in cell-based assays with no relevant cytotoxicity (Kühl et al 2020).…”
Section: Flavivirus Proteasementioning
confidence: 93%